The Influence of Sharia Values and Service Quality on Customer Loyalty with Customer Satisfaction as a Moderating Variable in the E-Commerce Industry - Isnaeni, Fajar; Hwihanus, Hwihanus (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study investigates the relationship between Sharia values, service quality, customer satisfaction, and customer loyalty in the context of e-commerce. Data was collected from 117 e-commerce customers through an online questionnaire. The analytical method used was Structural Equation Modeling (SEM) with the Smart PLS software. The results of the study indicate that Sharia values do not have a direct impact on customer loyalty but have a significant positive impact on customer satisfaction. Meanwhile, service quality does not have a direct effect on customer loyalty but has a strong influence on customer satisfaction. The findings also indicate that customer satisfaction significantly mediates the relationship between service quality and customer loyalty. These findings imply that e-commerce companies should improve service quality to enhance customer satisfaction, which in turn can strengthen e-commerce customer loyalty.